Empowerment of Orphanage Children through Ornamental Fish Cultivation Skills at Panti Asuhan Budi Mulya 2 Beringin Jaya Kemiling Bandar Lampung - Indariyanti, nur; JMB, Rietje; Huda Verdian, Aldi (Jurnal Pengabdian Nasional, 2022)
Budi Mulya2 (BM2) Orphanage is an orphanage located on Jalan Raden Imba Kusuma Ratu GangKenanga, Beringin Jaya Village, Kemiling District, Bandar Lampung. Problems faced by orphanagesinclude; the need for provision of life skills for foster children has not been fulfilled and there is a lackof cooperation with government or private agencies that can provide skills training programs for fosterchildren. Based on the analysis of the fishery sector, to help solve partner problems is to guideornamental fish cultivation and assistance in the establishment of ornamental fish farming businessunits that can be carried out on limited land. The purpose of this activity is the transfer of knowledgeand skills in ornamental fish cultivation which is expected to be a provision for independence andentrepreneurship. This service activity uses counseling and demonstration methods as well as practiceand giving stimulants. This activity received a positive response from the children's orphanage asindicated by the participation rate of almost 90%. The results of the evaluation of activities experiencedan increase in knowledge and skills by 23.2%. This shows that the counseling carried out is quite goodby the participants and can increase their knowledge and skills of the participants.